Antecedents of Sustainable Performance Mediated by Green Innovation in Water Treatment Companies in Indonesia - Yashashi Manuel Putra Sinaga; Dita Oki Berliyanti; B. Medina Nilasari (Cakrawala Repositori IMWI)
The increasing demand for sustainable business practices has encouraged water treatment companies to focus not only on economic performance but also on social and environmental responsibilities. The water treatment industry plays a strategic role in supporting water resource management, reducing environmental pollution, and contributing to the achievement of the Sustainable Development Goals (SDGs). Therefore, understanding the factors influencing sustainable performance is essential for ensuring long-term organizational sustainability. This study aimed to examine the influence of Green Human Resource Management (GHRM) and sustainable leadership on sustainable performance, with green innovation as a mediating variable in water treatment companies in Indonesia. This study employed a qualitative approach using a descriptive-exploratory research design. Data were collected through in-depth interviews, observations, and document analysis involving water treatment companies operating in Indonesia. Research informants included company leaders, human resource managers, and personnel responsible for sustainability and innovation initiatives. Data were analyzed using thematic analysis through data reduction, data display, and conclusion drawing. The findings indicated that the implementation of GHRM and sustainable leadership contributed significantly to sustainable performance by fostering an environmentally oriented organizational culture. Green innovation served as an important mechanism that strengthened this relationship through improved operational efficiency, waste reduction, resource optimization, and the development of environmentally friendly water treatment technologies. The study also revealed that sustainable performance was influenced by management commitment, employee involvement, and organizational capability to integrate green innovation into business strategies. The implications of this study contribute to the development of sustainability management literature and provide practical recommendations for water treatment companies in designing human resource management and leadership strategies that support long-term business sustainability.The increasing demand for sustainable business practices has encouraged water treatment companies to focus not only on economic performance but also on social and environmental responsibilities. The water treatment industry plays a strategic role in supporting water resource management, reducing environmental pollution, and contributing to the achievement of the Sustainable Development Goals (SDGs). Therefore, understanding the factors influencing sustainable performance is essential for ensuring long-term organizational sustainability. This study aimed to examine the influence of Green Human Resource Management (GHRM) and sustainable leadership on sustainable performance, with green innovation as a mediating variable in water treatment companies in Indonesia. This study employed a qualitative approach using a descriptive-exploratory research design. Data were collected through in-depth interviews, observations, and document analysis involving water treatment companies operating in Indonesia. Research informants included company leaders, human resource managers, and personnel responsible for sustainability and innovation initiatives. Data were analyzed using thematic analysis through data reduction, data display, and conclusion drawing. The findings indicated that the implementation of GHRM and sustainable leadership contributed significantly to sustainable performance by fostering an environmentally oriented organizational culture. Green innovation served as an important mechanism that strengthened this relationship through improved operational efficiency, waste reduction, resource optimization, and the development of environmentally friendly water treatment technologies. The study also revealed that sustainable performance was influenced by management commitment, employee involvement, and organizational capability to integrate green innovation into business strategies. The implications of this study contribute to the development of sustainability management literature and provide practical recommendations for water treatment companies in designing human resource management and leadership strategies that support long-term business sustainability.